Analyses of High‐Iron Sedimentary Bedrock and Diagenetic Features Observed With ChemCam at Vera Rubin Ridge, Gale Crater, Mars: Calibration and Characterization. Issue 10 (9th October 2020) - David, G.; Cousin, A.; Forni, O.; Meslin, P.‐Y.; Dehouck, E.; Mangold, N.; L'Haridon, J.; Rapin, W.; Gasnault, O.; Johnson, J. R.; Ollila, A. M.; Newell, A. R.; et al.
Abstract: Curiosity investigated a topographic rise named Vera Rubin Ridge (VRR) in Gale Crater, for which a distinct hematite‐like signature was observed from orbit. However, the Chemistry and Camera (ChemCam) and Alpha Particle x‐ray Spectrometer (APXS) instruments on board the rover did not record any significant iron enrichment in the bulk of the ridge compared to previous terrains. For this study, we have reverified ChemCam iron calibration at moderate abundances and developed more accurate calibrations at high‐iron abundances using iron‐oxide mixtures in a basaltic matrix in order to complete the ChemCam calibration database. The high‐iron calibration was first applied to the analysis of dark‐toned diagenetic features encountered at several locations on VRR, which showed that their chemical compositions are close to pure anhydrous iron oxides. Then, we tracked iron abundances in the VRR bedrock and demonstrated that although there is no overall iron enrichment in the bulk of the ridge (21.2 ± 1.8‐wt.% FeOT ) compared to underlying terrains, the iron content is more variable in its upper section with areas of enhanced iron abundances in the bedrock (up to 26.6 ± 0.85‐wt.% FeOT ). Since the observed variability in iron abundances does not conform to the stratigraphy, the involvement of diagenetic fluid circulation was likely. An in‐depth chemical study of these Fe‐rich rocks reveals that spatial gradients in redox potential (Eh) may have driven iron mobility and reactions that precipitated and accumulated iron oxides. We hypothesize that slightly reducing fluids were probably involved in transporting ferrous iron. Mobile Fe 2+ could have precipitated as iron oxides in more oxidizing conditions. Plain Language Summary: Curiosity investigated a positive relief ridge named Vera Rubin Ridge (VRR) located in the Gale Crater. Orbital data indicate the presence of hematite (an iron oxide) in this ridge. Surprisingly, no significant enrichment in iron was observed by the two rover instruments (Chemistry and Camera [ChemCam] and Alpha Particle x‐ray Spectrometer [APXS]) that determined the chemical compositions. Here, we have made a dedicated iron calibration for ChemCam Martian data for high‐iron abundances. For this, we prepared mixtures of basaltic powder and iron oxides (hematite, goethite, or magnetite) and analyzed them with a ChemCam laboratory unit. The objective was to increase the set of standards currently used for ChemCam iron quantification. This method has shown that dark‐toned concretions located in some VRR bedrock have an iron abundance similar to pure hematite. An iron survey along the ridge revealed that there is no overall enrichment compared to underlying terrains. However, iron abundances recorded in the upper part of the ridge are more variable. Areas of enhanced iron abundances do not follow the rock stratification, which suggests that the phenomenon responsible for the iron variability did not occur during the sediment deposition but rather occurred later, during diagenesis. Fluids percolating into the sediment are most likely responsible for iron mobility. Key Points: We present a dedicated ChemCam calibration for high‐iron abundances and apply it to Vera Rubin Ridge bedrock and diagenetic concretions Dark‐toned diagenetic features have iron contents close to pure anhydrous iron oxides Iron variability is observed among bedrock in the upper part of the ridge, attributed to iron mobility during diagenesis